2018
DOI: 10.1016/j.nmd.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous recessive MYH2 mutation mimicking dominant MYH2 associated myopathy

Abstract: Mutations in MYH2 that encodes myosin heavy chain IIa cause both dominant and recessively inherited myopathies. Patients with dominantly inherited MYH2 missense mutations present with ophthalmoplegia and progressive proximal limb weakness. Muscle biopsy reveals rimmed vacuoles and inclusions, prompting this entity to initially be described as hereditary inclusion body myopathy 3. In contrast, patients with recessive MYH2 mutations have early onset, non-progressive, diffuse weakness and ophthalmoplegia. Muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Previous ultrastructural studies have shown small cytoplasmic inclusions consisting of 15 and 20 nm tubulofilaments, Z-band streaming [1,3,19], disarrangement of sarcoplasmic myofilaments [13,27], and nuclear filamentous inclusions [30]. Similarly to other MYH2-myopathy cases, which have shown selective reduction in the number and size of type 2A muscle fibers [2,5,13,28], occasionally even leading to the lack of type 2A fibers [26], our patient showed paucity and atrophy of type 2A fibers, and severe reduction in MyHC-IIA expression. The coexistent nonspecific chronic myopathic changes, also present in our patient's muscle biopsy, are not novel, except for the ring fibers.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous ultrastructural studies have shown small cytoplasmic inclusions consisting of 15 and 20 nm tubulofilaments, Z-band streaming [1,3,19], disarrangement of sarcoplasmic myofilaments [13,27], and nuclear filamentous inclusions [30]. Similarly to other MYH2-myopathy cases, which have shown selective reduction in the number and size of type 2A muscle fibers [2,5,13,28], occasionally even leading to the lack of type 2A fibers [26], our patient showed paucity and atrophy of type 2A fibers, and severe reduction in MyHC-IIA expression. The coexistent nonspecific chronic myopathic changes, also present in our patient's muscle biopsy, are not novel, except for the ring fibers.…”
Section: Discussionmentioning
confidence: 88%
“…Pathogenic MYH2 variants have tended to cluster either within key functional domains in the motor head, or in the coiled-coil tail region as truncations [ 5 ]. Here we describe an additional two MYH2 variants within the catalytic head and tail domains, being only the second report [ 30 ] of variants spanning both regions simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first patients with recessive myosin IIa myopathy carried compound heterozygous or homozygous truncating variants in MYH2 [2]. Several additional cases have later been reported carrying either truncating or missense variants [3][4][5][6][7][8][9][10]. All described individuals so far have had external ophthalmoplegia and most have had ptosis and facial muscle weakness, in addition to usually proximal muscle weakness.…”
Section: Introductionmentioning
confidence: 96%